Night of the cobra : a sniper novel - Coughlin, Jack, 1966- (Coughlin, Jack, 1966- Sniper novel., 2015)
"Top-ranked Marine sniper Kyle Swanson was a promising young Marine on a dangerous peace-keeping mission in Mogadishu when he first captured "the Cobra", and it could have cost him his life--had it not been for the schoolteacher who risked her own to save him. Now Swanson is sent on a mission to track down two targets--one is the Cobra, the warlord who spent twenty years in prison after Swanson captured him and is now back in charge of the strong Somali underworld, vowing vengeance on the Marine; the other is the grandson of the schoolteacher who once saved his life, who has joined the Cobra's army of terror. The boy had been swept up in a Detroit-based Somali gang that terrorized the American Midwest and Canada before fleeing back to the protection of the Cobra. His grandmother swears he's innocent, but the CIA tells Kyle to kill him before taking out the Cobra. To find the truth and accomplish his mission, Swanson must return to the one place he had hoped he'd never see again, the daunting hovels of Mogadishu--where the Cobra lies in wait"--